2012
DOI: 10.26719/2012.18.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of dermatoses in Iraqi children

Abstract: The prevalence of paediatric dermatoses has risen in Iraq from 33.5% in 1987 to 40.9% in 2010. The objective of this study was to document the pattern of dermatoses in Iraqi children attending the outpatient clinic of a teaching hospital in Baghdad, Iraq. We conducted a cross-sectional study of 663 children under the age of 12 years who attended for dermatological consultation during 2008. The study showed that the prevailing dermatoses were as follow: infectious (32.3%), eczematous (20.8%), pigmentary (17.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
18
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
10
18
4
Order By: Relevance
“…In present study, Warts were the most common viral infection followed by Molluscum contagiosum(MC). In study conducted by M. D. Al-Mendalawi et al 5 and RitaVora et al 6 , warts are the most common viral infection which is followed by MC, which is consistent with the present study.…”
Section: Distribution Of Pediatric Dermatosessupporting
confidence: 82%
See 4 more Smart Citations
“…In present study, Warts were the most common viral infection followed by Molluscum contagiosum(MC). In study conducted by M. D. Al-Mendalawi et al 5 and RitaVora et al 6 , warts are the most common viral infection which is followed by MC, which is consistent with the present study.…”
Section: Distribution Of Pediatric Dermatosessupporting
confidence: 82%
“…In a study done by Iffat Hassan et al 7 ,Kaliaperumal Karthikeyan et al 9 and M.D. Al-Mendalawi et al 5 , have found similar pattern of fungal infections, which is in correlation with the present study. In present study, Warts were the most common viral infection followed by Molluscum contagiosum(MC).…”
Section: Distribution Of Pediatric Dermatosessupporting
confidence: 81%
See 3 more Smart Citations